Educational dialogue with patients in traumatology and orthopedics - Velázquez Tamez, Laura Elizabeth (Horizonte Sanitario, 2021)
Educational dialogue with patients in traumatology and orthopedics Abstract Introduction: This paper describes the educational dialogue with the patient and identifies teaching strategies and soft skills needed to make it happen. Method: first-order sampling with in depth interviews with specialists in traumatology and orthopedics with subsequent instrumental case analysis in second order sampling. Results: A four-step model is proposed to develop the educational dialogue with the patient. Teaching strategies and soft skills needed for doctors are identified to teach the patient to take care of their health. Conclusions: This model could guide the developing of this dialogue. Educational dialogue could reduce the conflicts in this medical specialty. It is suggested to deepen the teaching of these skills in medical training.